Penguatan Nalar Kritis Siswa Melalui Nilai Profil Pancasila Madrasah Aliyah Neegeri 3 Kota Pekanbaru - Widodo, Widodo; Firdaus, Firdaus; Sholeh, A; Alfaturrahman, Alfaturrahman; Muranaki Tarigan, Targer (Al-ihsan: Jurnal Pengabdian Agama Islam, 2026)
The critical thinking skills of students are a potential that can be developed to achieve excellence. The community service method is carried out in five stages, namely: socialization, training, utilization of technology, mentoring & evaluation, and sustainable programs. The purpose of community service is to strengthen the critical thinking skills of students through the values of the Pancasila profile at MAN 3 Pekanbaru City. The results of the study show that the strengthening of critical thinking at MAN 3 Pekanbaru City is carried out through: socialization and integration in problem-based learning by utilizing technology, mentoring through reflective dialogue in P5RA activities, and process-based evaluation using character development rubrics. The sustainable program is able to change students' mindset from passive information recipients to analytical thinkers who are positively skeptical of social issues in their surroundings.